Green Intellectual Capital And Sustained Competitive Advantages In The Industrial Sector Of Indonesia - Solihin Solihin; Harnovinsah Harnovinsah; Tugiantoro Tugiantoro; Karsam Karsam (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: The purpose of this study is to examine the effect of Green Intellectual Capital which includes three components namely green human capital, green structural capital, and green relational capital on sustainable competitive advantage through   h moderation of environmental consciousness in the manufacturing industry in Indonesia, which has been listed on the Indonesia Stock Exchange. Methodology/approach: This research is a quantitative study, the number of samples used is 216 of 316 populations of high-profile sensitive industries listed on the Indonesia Stock Exchange. The survey was conducted at a managerial level with a minimum of 3 years experiences. This study used a questionnaire instrument with a purposive sampling method and data analysis using Structured Equation Modelling (SEM-PLS) Findings: The empirical results of this study indicate that the three components of green human capital, green structural capital, and green relational capital have proven to have a significant effect on sustainable competitive advantage. While testing through environmental consciousness moderation shows that the three components of green human capital, green structural capital, and green relational capital, have no significant effect on sustainable competitive advantage. The implication of this research is that green intellectual capital can be used as a guide for companies that can ultimately develop and maintain a sustainable competitive advantage. Practical implications:  The green human capital can be use as guidance of companies that can ultimately develop and mantaian the competitive advantage Originality/value: The originality of this research is the variable of green intellectual capital and competitive advantage in winning the competitive strategy for companies, the research results that the sustainable competitive advantage which will be the focus of study for the next researcher.